Emerging trends in the photodynamic inactivation (PDI) applied to the food decontamination. (June 2021) - Cossu, Marco; Ledda, Luigi; Cossu, Andrea
Graphical abstract: Highlights: The PDI has been reviewed as an optimised non-thermal food disinfection process. Food sanitation is achieved by the activation of endogenous PS with blue LED light. Curcumin and porphyrins are becoming leading PS for the PDI in food matrices. PDI is a sustainable technology characterised by energy and water cost saving. PDI is a promising technology among the low-cost non-thermal food sanitation methods. Abstract: The food and drink manufacturing industry is constantly seeking for alternative sanitation and disinfection systems that may achieve the same antimicrobial efficiency of conventional chemical sanitisers and at the same time be convenient in terms of energy and water savings. A candidate technology for this purpose is the use of light in combination with photosensitisers (PS) to generate a bioactive effect against microbial agents in a process defined as photodynamic inactivation (PDI). This technology can be applied to the food processing of different food matrices to reduce the microbial load of foodborne pathogens such as bacteria, fungi, viruses and protozoa. Also, the PDI can be exploited to increase the shelf-life period of food by inactivation of spoiling microbes. This review analyses new developments in the last five years for PDI systems applied to the food decontamination from foodborne pathogens. The photosensitisation mechanisms and methods are reported to introduce the applied technology against microbial targets in food matrices. Recent blue light emitting diodes (LED) lamp systems for the PDI mediated by endogenous PS are discussed as well PDI technologies with the use of exogenous PS from plant sources such as curcumin and porphyrin-based molecules. The updated overview of the most recent developments in the PDI technology both in wavelengths and employed PS will provide further points of analysis for the advancement of the research on new competitive and effective disinfection systems in the food industry.